HOW TO ENHANCE WRITING SKILLS OF EFL STUDENTS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Developing strong writing skills is essential for students to succeed academically and professionally. This article explores a comprehensive approach to enhancing the writing abilities of students, covering strategies to improve language proficiency, organization and structure, creativity and critical thinking, effective feedback, and the integration of technology. By implementing these multifaceted techniques, students can become more confident, effective, and engaging writers, better prepared for their future endeavors.